Observation of multiple hard photon final states at root s=130-140 GeV at LEP - Acciarri, M; Adam, A; Adriani, O; AguilarBenitez, M; Ahlen, S; Alpat, B; Alcaraz, J; Alemanni, G; Allaby, J; Aloisio, A; Alverson, G; Alviggi, MG; et al. (1996)
We have studied the process e+e- → ny (n ≥ 2) at an average center-of-mass energy of 133 GeV using the L3 detector at LEP. For an integrated luminosity of 4.95 pb-1 we find one γγγγ(γ) final state with only hard photons. The rates of both γγγ and γγ events are consistent with QED expectations. The cross section of the reaction e+e- → γγ(γ) in the polar range 16° < θγ < 164° is measured to be 22.6 ± 2.2 pb. Decays into photons of narrow scalar resonances with masses between 90 and 130 GeV are not observed. The observation of the event with four energetic photons is consistent with QED although the kinematic configuration of the photons is atypical.